Urbanization Dynamics and Socio‑Economic Changes in Surabaya City - Maulana, Ilham Nur Hanifan; Wahyudi, Lydia Graceanova (Public Policy and Management Inquiry, 2025)
The phenomenon of urbanization in Indonesia's big cities, particularly Surabaya, is leading to significant social and economic changes. The increasing population in urban areas is driven by development inequality, better job opportunities, and improved social facilities. However, urbanization also presents challenges such as unemployment, social inequality, and the rise of slum areas. This article focuses on analyzing the impact of urbanization on Surabaya's socio-economic structure and developing effective public policies to manage this phenomenon. The research emphasizes the importance of data- driven policy interventions that consider infrastructure requirements, public services, and community participation. Collaboration between the government, private sector, and civil society is crucial for formulating successful solutions. While urbanization can drive economic growth, it is important to urgently address its negative impacts. With proper planning and the right policies, Surabaya can overcome these challenges, enhance residents' quality of life, and ensure equitable distribution of economic benefits.